Oxford New syllabus Mathematics book 4 (7th edition) - Yeo Joseph (Pakistan ` oxford university press, 2018)
New Syllabus Mathematics (NSM) is a series of textbooks where the inclusion of valuable learning experiences, as well as the integration of real-life applications of learnt concepts serve to engage the hearts and minds of students sitting for the GCE O-level examination in Mathematics. The series covers the new Cambridge O Level Mathematics ( Syllabus D) 4024/4029 for examinations in 2018, 2019, and 2020. The newly formatted questions which require application of mathematical techniques to solve problems have been inducted. Special Features Chapter Opener to arouse students$1 (Binterest and curiosity Learning Objectives for students to monitor their own progress Investigation, Class Discussion, Thinking Time, Journal Writing and Performance Task for students to develop requisite skills, knowledge and attitudes Worked Examples to show students the application of concepts Practise Now for immediate practice Similar Questions for teachers to choose questions that require similar application of concepts Exercise classified into Basic, Intermediate and Advanced to cater to students with different learning abilities Summary to help students consolidate concepts learnt Review Exercise to consolidate the learning of concepts Challenge Yourself to challenge high-ability students Revision Exercises to help students assess their learning after every few chapterss
this book is a part of new syllabus mathematics series, designed to align with modern mathematics curriculum. it includes comprehensive explanations, exercises and real - world application. additional resources such as teacher's guide, solution manual and online materials may be available to support learning and instructions.
Keywords: Maths - text book